STUDY OF THE PROBLEM OF TRAINING THE FUTURE TEACHER OF NATURAL DISCIPLINES FOR THE ORGANIZATION OF GROUP EDUCATIONAL ACTIVITIES - Мороз, Л.М.; Мельничук, О.Д. (Modern engineering and innovative technologies, 2024)
The article determines that group educational activity contributes to the improvement of students’ success, solves educational and developmental tasks. The search for optimal forms of organization of students’ educational activities, the use of active lea